Glycine Receptor Activation Impairs ATP-Induced Calcium Transients in Cultured Cortical Astrocytes - Morais, Tatiana P.; Coelho, David; Vaz, Sandra H.; Sebastião, Ana M.; Valente, Cláudia A. (Frontiers in Molecular Neuroscience, 2018)
In central nervous system, glycine receptor (GlyR) is mostly expressed in the spinal cord and brainstem, but glycinergic transmission related elements have also been identified in the brain. Astrocytes are active elements at the tripartite synapse, being responsible for the maintenance of brain homeostasis and for the fine-tuning of synaptic activity. These cells communicate, spontaneously or in response to a stimulus, by elevations in their cytosolic calcium (calcium transients, Ca2+T) that can be propagated to other cells. How these Ca2+T are negatively modulated is yet poorly understood. In this work, we evaluated GlyR expression and its role on calcium signalling modulation in rat brain astrocytes. We first proved that GlyR, predominantly subunits α2 and β, was expressed in brain astrocytes and its localization was confirmed in the cytoplasm and astrocytic processes by immunohistochemistry assays. Calcium imaging experiments in cultured astrocytes showed that glycine (500 µM), a GlyR agonist, caused a concentration-dependent reduction in ATP-induced Ca2+T, an effect abolished by the GlyR antagonist, strychnine (0.8 µM), as well as by nocodazole (1 μM), known to impair GlyR anchorage to the plasma membrane. This effect was mimicked by activation of GABAAR, another Cl--permeable channel. In summary, we demonstrated that GlyR activation in astrocytes mediates an inhibitory effect upon ATP induced Ca2+T, which most probably involves changes in membrane permeability to Cl- and requires GlyR anchorage at the plasma membrane. GlyR in astrocytes may thus be part of an inhibitory feedback loop to refrain astrocyte-to-neuron communication.